2024
DOI: 10.1002/fsn3.4131
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing fungal treatment of lignocellulosic agro‐industrial by‐products to enhance their nutritional value

Mohamed Benaddou,
Hassan Hajjaj,
Aimad Allali
et al.

Abstract: This study delves into the dynamic interaction between various fungal strains, substrates, and treatment durations to optimize the nutritional value of these by‐products. Six fungi, including Penicillium chrysogenum, Fusarium sp., Fusarium oxysporum, Fusarium solani, Penicillium crustosum, and Cosmospora viridescens, were evaluated across three substrates: wheat straw (WS), cedar sawdust (CW), and olive pomace (OP) over treatment periods of 4, 8, and 12 weeks. The study discerned profound impacts of these fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…After being infected with F. solani , the cellulose and hemicellulose content in wood will decrease ( Rahmawati et al, 2020 ). Benaddou et al (2024) experiment revealed that F. oxysporum and F. solani were the most selective lignin-degrading fungi among the tested fungi. The cell wall degrading enzyme (CWDE) in Fusarium is the main pathogenic factor for its invasion and infection of plants, mainly including pectinase, cellulase, and protease ( Erazo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…After being infected with F. solani , the cellulose and hemicellulose content in wood will decrease ( Rahmawati et al, 2020 ). Benaddou et al (2024) experiment revealed that F. oxysporum and F. solani were the most selective lignin-degrading fungi among the tested fungi. The cell wall degrading enzyme (CWDE) in Fusarium is the main pathogenic factor for its invasion and infection of plants, mainly including pectinase, cellulase, and protease ( Erazo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%